Behavioral Deficits in Animal Models of Blast Traumatic Brain Injury - Aravind, Aswati; Ravula, Arun Reddy; Chandra, Namas; Pfister, Bryan J. (Frontiers in Neurology, 2020)
Blast exposure has been identified to be the most common cause for traumatic brain injury (TBI) in soldiers. Over the years, rodent models to mimic blast exposures and the behavioral outcomes observed in veterans have been developed extensively. However, blast tube design and varying experimental parameters lead to inconsistencies in the behavioral outcomes reported across research laboratories. This review aims to curate the behavioral outcomes reported in rodent models of blast TBI using shock wave tubes or open field detonations between the years 2008-2019 and highlight the important experimental parameters that affect behavioral outcome. Further, we discuss the role of various design parameters of the blast tube that can affect the nature of blast exposure experienced by the rodents. Finally, we assess the most common behavioral tests done to measure cognitive, motor, anxiety, auditory and fear conditioning deficits in blast TBI (bTBI) and discuss the advantages and disadvantages of these tests.